Gender differences in climate-smart adaptation practices amongst bean-producing farmers in Malawi: The case of Linthipe Extension Planning Area - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu (2024)
The study aimed to understand the gender differences in access to and use of climate-smart adaptation practices among bean-producing farmers in the Dedza District, Malawi. The scope of the study covered 246 households across 14 villages, focusing on how men, women, and youth adopt climate-smart agricultural (CSA) technologies. It addressed the challenges farmers face, the CSA interventions implemented, and how these practices are linked to food and income security. Principal Investigators aimed to answer questions about the influence of socio-demographic, farm-level, and institutional factors on CSA adoption​The study aimed to understand the gender differences in access to and use of climate-smart adaptation practices among bean-producing farmers in the Dedza District, Malawi. The scope of the study covered 246 households across 14 villages, focusing on how men, women, and youth adopt climate-smart agricultural (CSA) technologies. It addressed the challenges farmers face, the CSA interventions implemented, and how these practices are linked to food and income security. Principal Investigators aimed to answer questions about the influence of socio-demographic, farm-level, and institutional factors on CSA adoption​The study aimed to understand the gender differences in access to and use of climate-smart adaptation practices among bean-producing farmers in the Dedza District, Malawi. The scope of the study covered 246 households across 14 villages, focusing on how men, women, and youth adopt climate-smart agricultural (CSA) technologies. It addressed the challenges farmers face, the CSA interventions implemented, and how these practices are linked to food and income security. Principal Investigators aimed to answer questions about the influence of socio-demographic, farm-level, and institutional factors on CSA adoption​The study aimed to understand the gender differences in access to and use of climate-smart adaptation practices among bean-producing farmers in the Dedza District, Malawi. The scope of the study covered 246 households across 14 villages, focusing on how men, women, and youth adopt climate-smart agricultural (CSA) technologies. It addressed the challenges farmers face, the CSA interventions implemented, and how these practices are linked to food and income security. Principal Investigators aimed to answer questions about the influence of socio-demographic, farm-level, and institutional factors on CSA adoption​ Methodology: The study utilized a quantitative approach with data collected through structured questionnaires administered to 246 randomly sampled households across 14 villages in Dedza District, Malawi. The survey covered socio-demographic characteristics, land access, bean production practices, and constraints, as well as access to information and markets. Data were analyzed using the multivariate probit model, which examined the influence of various factors on simultaneous adoption​ of CSA practices..The study utilized a quantitative approach with data collected through structured questionnaires administered to 246 randomly sampled households across 14 villages in Dedza District, Malawi. The survey covered socio-demographic characteristics, land access, bean production practices, and constraints, as well as access to information and markets. Data were analyzed using the multivariate probit model, which examined the influence of various factors on simultaneous adoption​ of CSA practices..The study utilized a quantitative approach with data collected through structured questionnaires administered to 246 randomly sampled households across 14 villages in Dedza District, Malawi. The survey covered socio-demographic characteristics, land access, bean production practices, and constraints, as well as access to information and markets. Data were analyzed using the multivariate probit model, which examined the influence of various factors on simultaneous adoption​ of CSA practices..The study utilized a quantitative approach with data collected through structured questionnaires administered to 246 randomly sampled households across 14 villages in Dedza District, Malawi. The survey covered socio-demographic characteristics, land access, bean production practices, and constraints, as well as access to information and markets. Data were analyzed using the multivariate probit model, which examined the influence of various factors on simultaneous adoption​ of CSA practices..